Mathematics in its relation to other disciplines. Some examples related to economics and physics - Jean-Luc Dorier (El Cálculo y su Enseñanza)
Mathematics is often seen as a very specific subject, either by students, parents, media or even mathematicians themselves. In many contexts, mathematics is feared and seen as a subject for selection, disconnected from interesting applications to real life. Moreover, the structure of teaching institutions, in many cases, makes the collaboration between teachers from different disciplines very difficult. At the same time, mathematics is more and more invisible in everyday life, since high technology tends to hide the mathematics necessary for its creation in sophisticated black boxes. As a result, it is quite a challenge to give an adequate answer to those who, legitimately, wonder what mathematics is useful for.